Mitochondrial DNA D-loop diversity of Tibetan pig populations - Ting Jiao (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2009)
The Tibetan pig, a plateau type pig breed, is recognized as one of the most important pig breeds in China and a valuable genetic resource worldwide. As part of an initial step to investigate the genetic structure and diversity of its populations, phylogenetic analysis was carried out using 417bp mitochondrial DNA (mtDNA) D-loop sequence variations. The mtDNA breed sequences of 26 Hezuo Tibetan pigs were found to be distributed in 20 haplotypes, 19 of which were unique to this breed. The nucleotide diversity within the control region sequences of Hezuo Tibetan pigs (0.82%) was found to be higher than those of the other Tibetan pig populations sampled in this study. Based on the results, conservation of Hezuo Tibetan pigs should be a priority as the breed serves as a vector of unique genetic resources. Rooted neighbor-joining tree and median joining network procedures carried out on the data showed that the Tibetan pig breed has three major ancestral maternal origins and different domestication histories.